2021
DOI: 10.1177/17562864211030365
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival analysis of masitinib in amyotrophic lateral sclerosis

Abstract: Background: A randomized, placebo-controlled phase III study (AB10015) previously demonstrated that orally administered masitinib (4.5 mg/kg/day) slowed rate of functional decline, with acceptable safety, in amyotrophic lateral sclerosis (ALS) patients having an ALS Functional Rating Scale-revised (ALSFRS-R) progression rate from disease onset to baseline of <1.1 points/month. Here we assess long-term overall survival (OS) data of all participants from study AB10015 and test whether a signal in OS is eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…The current investigation was conducted to determine the major P450 enzymes involved in the metabolism and bioactivation of masitinib, a tyrosine kinase inhibitor under clinical investigation for diverse therapeutic areas, including neurodegenerative diseases, , mast cell disorders, and COVID-19 . Masitinib is a structural analogue of the widely used anticancer tyrosine kinase inhibitor imatinib, but studies suggest that masitinib may have unique therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current investigation was conducted to determine the major P450 enzymes involved in the metabolism and bioactivation of masitinib, a tyrosine kinase inhibitor under clinical investigation for diverse therapeutic areas, including neurodegenerative diseases, , mast cell disorders, and COVID-19 . Masitinib is a structural analogue of the widely used anticancer tyrosine kinase inhibitor imatinib, but studies suggest that masitinib may have unique therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Masitinib is a small molecule tyrosine kinase inhibitor of stem cell growth factor receptor KIT and platelet-derived growth factor receptors along with Lyn and Fyn kinases. , Masitinib has been studied as an investigational drug for the treatment of amyotrophic lateral sclerosis (ALS), , gastrointestinal stromal tumors, Alzheimer’s disease, multiple sclerosis, , and mastocytosis . Masitinib is currently used in veterinary medicine for the treatment of mast cell tumors in dogs .…”
Section: Introductionmentioning
confidence: 99%
“…Dose‐escalation also applies to the main forerunner competing drug so‐called Imatinib – a Tyrosine Kinases (TKs) inhibitor involved in cancer and other proliferative disorders – used against amyotrophic lateral sclerosis (Soria et al, 2009; Mora et al, 2021). That is to say, regardless of the uncertain future of the MD1003, especially in Phase III (to evaluate how the new medication works in comparison to existing medications for the same condition), dose‐escalation remains at the very heart of the extension framework.…”
Section: Field Investigations and Findings: Towards A General Ai‐base...mentioning
confidence: 99%
“…This pictures how the extension framework leads to a novel representation generalizing both the (meta-)structure and the identity of things and phenomena while including any prior representation as a sub-one. We can draw a close parallel here with the geometrization of space (see subsection 1.2) Dose-escalation also applies to the main forerunner competing drug so-called Imatiniba Tyrosine Kinases (TKs) inhibitor involved in cancer and other proliferative disordersused against amyotrophic lateral sclerosis (Soria et al, 2009;Mora et al, 2021). That is to say, regardless of the uncertain future of the MD1003, especially in Phase III (to evaluate how the new medication works in comparison to existing medications for the same condition), dose-escalation remains at the very heart of the extension framework.…”
Section: General Extension Framework Redefining the Universe Of Possi...mentioning
confidence: 99%
“…The results from an international, phase 2/3, placebo-controlled trial in 394 adult patients with ALS showed that masitinib combined with riluzole could significantly slow the deterioration of ALSFRS-R scores by 27% ( Mora et al, 2020 ). The long-term overall survival analysis indicated that oral masitinib, if delivered early, could prolong survival by 2 years and decrease the mortality rate by 44% ( Mora et al, 2021 ). Moreover, a phase-3, multicenter, placebo-controlled, double-blind, randomized trial (NCT03127267) will compare the efficacy and safety of masitinib in combination with riluzole in 495 patients with ALS from 13 countries (United States, Denmark, France, Germany, Israel, Russian, Ukraine, etc., mainly American and European cohorts), sponsored by AB Science.…”
Section: Drugsmentioning
confidence: 99%